Resistance response of cowpea accessions to charcoal rot - Tomaz, Francisco Linco de Souza (2025)
The objective of this study was to assess the resistance reaction of cowpea accessions grown in municipalities of Rio Grande do Norte, Brazil, to the fungus Macrophomina phaseolina (Tassi) Goid. A total of 53 cowpea accessions were evaluated in two greenhouse experiments (25 and 28 accessions, respectively), using a completely randomized design with five replications; each replication consisted of one plant per pot. The fungus was isolated from cowpea plants showing charcoal rot symptoms. Fungi were cultured and purified on a potato-dextrose-agar (PDA) medium with tetracycline (0.05 mg mL-1) and then inoculated into cowpea plants using the toothpick method. Inoculation was carried out when the plants exhibited two true leaves. The disease response of accessions was evaluated 30 days after inoculation based on a disease severity scale. Transformed data were subjected to analysis of variance, and means were grouped using the Scott-Knott test (p < 0.05). Accessions 6, 14, 17, 30, 42, 43, 46, 48, and 50 were highly resistant to M. phaseolina and, therefore, can be included in breeding programs focused on resistance to pathogens. The results indicate a predominance of genes conferring resistance to M. phaseolina in cowpea accessions from the Agreste mesoregion of Rio Grande do Norte, Brazil.